The role of clinical psychologist in treatment of psychosomatic disorders - Nikolay A. Shevchenko (LLC "MEDIAFORMAT", 2022)
Clinical psychology is an interdisciplinary scientific and practical area of activity that is currently viewed as essential for comprehensive approach to therapy and rehabilitation of patients with various disorders. The paper describes the role of clinical psychologist in working with psychosomatic patients; the clinical psychologist's responsibilities and the differences between these specialists and representatives of related specialties are also explained.